2013
DOI: 10.1021/jo4012656
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Aminolytic Kinetic Resolution of Racemic Epoxides Using Recyclable Chiral Polymeric Co(III)-Salen Complexes: A Protocol for Total Utilization of Racemic Epoxide in the Synthesis of (R)-Naftopidil and (S)-Propranolol

Abstract: Chiral polymeric Co(III) salen complexes with chiral ((R)/(S)-BINOL, diethyl tartrate) and achiral (piperazine and trigol) linkers with varying stereogenic centers were synthesized for the first time and used as catalysts for aminolytic kinetic resolution (AKR) of a variety of terminal epoxides and glycidyl ethers to get enantio-pure epoxides (ee, 99%) and N-protected β-amino alcohols (ee, 99%) with quantitative yield in 16 h at RT under optimized reaction conditions. This protocol was also used for the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Preliminary results suggested that all these complexes except complex 5 (ee, 72%) were showing good activity and moderate to good enantioselectivity in asymmetric HKR of 1,2epoxyhexane. A possible explanation for less reactivity of complex 5 was provided by us in an earlier report, 22 as the distortions (random twists) in the structure of the polymeric salen ligand in case of ligand 5' prepared from racemic BINOL where both R-and S-BINOL motifs may perhaps present randomly in a single polymeric chain.…”
Section: Resultsmentioning
confidence: 92%
“…Preliminary results suggested that all these complexes except complex 5 (ee, 72%) were showing good activity and moderate to good enantioselectivity in asymmetric HKR of 1,2epoxyhexane. A possible explanation for less reactivity of complex 5 was provided by us in an earlier report, 22 as the distortions (random twists) in the structure of the polymeric salen ligand in case of ligand 5' prepared from racemic BINOL where both R-and S-BINOL motifs may perhaps present randomly in a single polymeric chain.…”
Section: Resultsmentioning
confidence: 92%
“…Consequently, numerous disalicylaldehydes have been prepared, possessing mostly tert ‐butyl groups in the ortho position of the phenolic group to ensure high enantioselectivities, and therefore interconnected in the para position, away from the active catalytic sites, with a large variety of spacers. The group of Kureshy prepared dialdehydes with linkers possessing additional stereogenic centers from binaphthol or diethyltartrate derivatives, or free of them but having different flexibility properties . Nucleophilic substitution was readily performed between the engaged diols or diamines with chloromethylsalicylaldehyde, and condensation occurred subsequently with enantiopure cyclohexyldiamine to deliver linear chiral polymers (Scheme ) which were characterized by classical methods and GPC analyses, revealing a high molecular weight and a narrow polymer distribution index.…”
Section: Polymerization Of Salen Derivativesmentioning
confidence: 99%
“…The group of Kureshy prepared dialdehydes with linkers possessing additional stereogenic centers from binaphthol or diethyltartrate derivatives, or free of them but having different flexibility properties. [49] Nucleophilic substitution was readily performed between the engaged diols or diamines with chloromethylsalicylaldehyde, and condensation occurred subsequently with enantiopure cyclohexyldiamine to deliver linear chiral polymers (Scheme 14) which were characterized by classical methods and GPC analyses, revealing a high molecular weight and a narrow polymer distribution index. After introduction of cobalt salts, these polymers were tested to catalyze the asymmetric kinetic aminolysis of various epoxides.…”
Section: Polymerization Of Salen Derivativesmentioning
confidence: 99%
“…Some quinazoline-type ligands or their metal complexes are used as biological models for understanding the structure of biomolecules and biological processes [12][13][14], and have high selectivity recognition [15] and catalytic activity [16,17]. Acetate ions often play an important role in coordination chemistry, adopting binding modes such as terminal monodentate or chelating to one metal center [18]. Cobalt(II) complexes have been widely investigated [19][20][21], but cleavage of two C-N bonds of Schiff base-type ligands have not been observed.…”
Section: Introductionmentioning
confidence: 99%